Azobenzene‐Based Photomechanical Biomaterials. Issue 9 (11th July 2021) - Sun, Jing; Wang, Fan; Zhang, Hongjie; Liu, Kai
Abstract : Biomaterials with stimuli sensitivity and good mechanical properties are garnering interest as an important branch of stimuli‐responsive materials. Among them, photomechanical biomaterials are an emerging class of eco‐friendly materials for the development of various biomedical devices because they offer high spatiotemporal control, on‐demand response, and noninvasive manipulation. In particular, azobenzene can be reversibly converted from the trans to the cis isomer under irradiation by different wavelengths of light. The significant changes in structural geometry and excellent fatigue resistance of azobenzene upon isomerization allow its use in the fabrication of materials with photoresponsive properties, such as bending, twisting, coiling, buckling, expansion, or even jumping. However, studies on the photomodulated mechanical performance of azobenzene‐based bulk biomaterials have rarely been reported. This review focuses on the photomechanical effects that occur in various systems incorporated with azobenzene moieties. Within this framework, the advantages of azobenzene in different photomechanical materials, including liquid crystals, bulk films, gels, and bulk fibers, are discussed. In each section, the light‐induced modulation of mechanical properties, including tensile strength, modulus, and toughness, is highlighted. Finally, a summary and outlook for the development of azobenzene‐based photomechanical materials is presented. Abstract : The photo‐mechanical effects that occur in various systems with incorporated azobenzene moieties are summarized. Various photomechanical materials from liquid crystal, bulk film, gel to bulk fiber are discussed in detail. The photo‐modulation of material's mechanics including tensile strength, modulus, and toughness is highlighted. Perspectives and challenges in the field of azobenzene‐based photomechanical materials are also presented.